Contribution of Energy Dysfunction to Impaired Protein Translation in Neurodegenerative Diseases - Liu, Yu-Ju; Chern, Yijuang (Frontiers in Cellular Neuroscience, 2021)
Impaired energy homeostasis and aberrant translational control have independently been implicated in the pathogenesis of neurodegenerative diseases. AMP kinase (AMPK), regulated by the ratio of cellular AMP and ATP, is a major gatekeeper for cellular energy homeostasis. Abnormal regulation of AMPK has been reported in several neurodegenerative diseases, including Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS). Most importantly, AMPK activation is known to suppress the translational machinery by inhibiting the mechanistic target of rapamycin complex 1 (mTORC1), activating translational regulators, and phosphorylating nuclear transporter factors. In this review, we describe recent findings on the emerging role of protein translation impairment caused by energy dysregulation in neurodegenerative diseases.